Hf-induced strengthening and lattice distortion in HfxNbTaTiV refractory multi-principal element alloys - Yingwu Wang; Kai Xiong; Wei Li; Chengchen Jin; Haijun Wu; Hua Dai; Zihang Yang; Hongmo Yang; Shunmeng Zhang (Journal of Materials Research and Technology)
Refractory multi-principal element alloys (RMPEAs) are promising for high-temperature applications because of their excellent mechanical properties. Developing RMPEAs with both high strength and ductility is a key priority in materials science. Previous studies have emphasized hafnium's (Hf) crucial role in enhancing the strength and maintaining ductility of RMPEAs at room temperatures. However, the strengthening mechanisms induced by Hf are not fully understood and require further investigation. To address this, a series of HfxNbTaTiV alloys with varying Hf concentration were designed and investigated by combining experiments with theoretical calculations. The alloys prepared by vacuum arc melting present body-centered cubic solid solutions, high tensile strength, and good ductility at room temperature. The addition of Hf substantially increases the alloys' tensile strength and hardness. Theoretical analyses indicate that solid solution strengthening is the primary mechanism responsible for strengthening these alloys. The increase of lattice distortion induced by Hf addition plays a key role in strengthening RMPEAs. This study not only clarifies the effects of Hf addition on the phase formation, lattice distortion, and strengthening mechanisms of HfxNbTaTiV alloys, but also offers valuable insights for designing RMPEAs with high strength and ambient ductility.